The evolution of Turkish-Russian relations in the 21st century: the potential for pragmatism - Baichorov, Aleksandr M.; Deniz, Ali Hazer (Journal of the Belarusian State University. International Relations, 2022)
The article presents an overview of the Turkish foreign policy strategy and its implications for the development of Turkish-Russian relations. The bilateral relationship is viewed in the context of the Turkish-Russian summit of 2021 which became an important landmark gave an impetus to the future growth of the Turkish-Russian relationship. The influence of the international context on the Turkish-Russian rapprochement is also addressed.